Real-World Outcomes of Belantamab Mafodotin for Relapsed/Refractory Multiple Myeloma (RRMM): Preliminary Results of a Spanish Expanded Access Program (EAP) - Adrián Alegre; Gonzalo Benzo; Rafael Alonso; Joaquín Martínez-López; Ana Jimenez-Ubieto; Clara Cuéllar; Elham Askari; Elena Prieto; Concepción Aláez; Beatriz Aguado; Alberto Velasco; Isabel Krsnik; et al. (Oncology and Therapy, 2022)
Abstract Introduction Belantamab mafodotin (BM) is a new anti-BCMA antibody–drug conjugate, recently approved for triple-class relapsed and refractory multiple myeloma (RRMM). We assessed real-world outcomes with BM in patients under the Spanish Expanded Access Program (EAP). Methods We conducted an observational, retrospective, multicenter study including RRMM patients who received ≥ 1 dose of BM (Nov 2019 to Jun 2021). The primary endpoint was overall response rate (ORR). Secondary endpoints were progression-free survival (PFS), overall survival (OS), and incidence of treatment-emergent adverse events (TEAEs). Results Thirty-three patients were included with a median of 70 years of age (range, 46–79 years). Median time from diagnosis was 71 months (range, 10–858 months). Median prior lines was 5 (range, 3–8 lines); 90% of patients were triple-/quad-/penta-refractory; 48% showed high-risk cytogenetics. Median BM doses was 3 (range 1–16 doses), with a median follow-up of 11 months (6–15 months). ORR was 42.2% (≥ VGPR, 18.2%). Median PFS was 3 months (95% CI 0.92–5.08) in the overall population, and 11 months (HR 0.26; 95% CI 0.10–0.68) for patients who achieved ≥ PR. PFS was not significantly different according to age, cytogenetic risk, and prior therapy lines. OS was 424 days (95% CI 107–740). Non-hematological TEAEs (57.6% of patients; 30.3% ≥ G3) included keratopathy (51.5%; 21.2% ≥ G3) and patient-reported vision-related symptoms (45.5%). Keratopathy was resolved in 70.6% of patients. G3 hematological TEAEs was 18.2%, thrombocytopenia (21.2%). Dose reductions due to TEAEs: 30.3%; delays: 36.4%. Treatment discontinuation causes: progression (54.5%), toxicity (non-ocular; 6%/ocular; 6% /ocular + non-ocular toxicity; 3%), death (6%), and patient’s decision (3%). Conclusions BM showed relevant anti-myeloma activity in RRMM with a manageable safety profile. These results corroborate those observed in the BM pivotal trial.